Case report: Alcoholic fatty liver associated with low alcohol intake - Pasqualli, Aline Lourdes; Cabral, Raphaela Lorrana Rodrigues Araújo; Merlos, Priscila Gabriella Carraro; Merlos, Fernando (Seven Editora, 2024)
Alcoholic liver disease is common in patients with increased alcohol intake, as a result of which liver damage and injury occurs that can impair proper functioning and metabolization in the liver. The objective of this study is to present the case of a female patient who developed alcoholic fatty liver disease, but with low alcohol intake. The patient presented laboratory and imaging tests with significant alterations, and some hypotheses were raised for differential diagnoses, following the investigation, a biopsy was performed with a favorable result for alcoholic hepatic steatosis. Thus, it is of great importance to recognize that females reach higher alcohol concentrations when compared to males, in addition to having a hormonal issue involved. DOI:https://doi.org/10.56238/sevened2024.018-076